Mortality from cardiovascular diseases in the municipalities of mainland Portugal: spatiotemporal evolution between 1991 and 2017 - Ricardo Almendra; Paula Santana (Geography, Environment, Sustainability, 2020)
During the last decades, important efforts have been taken to tackle cardiovascular diseases, which resulted in important mortality and disability decreases. Despite this, cardiovascular diseases are still one of the major causes of death in Portugal. Thus, the aim of this study is to analyse the evolution of the spatial pattern of deaths by cardiovascular diseases, between 1991 and 2017, identifying areas of high risk, and its variation, in the 278 municipalities of Continental Portugal.Secondary data on annual resident population and deaths by cardiovascular diseases (International Classification of Diseases 10th revision: I00-I99) was collected from the Portuguese National Statistics for the municipalities of Portugal Mainland, from the period under analysis.To identify areas with significant high and low risk of mortality by cardiovascular diseases, towards time and space, and areas with significantly high or low temporal trends, retrospective spatial-temporal cluster and a spatial variation in temporal trends analysis were conducted.In the spatial-temporal analysis 3 clusters of high risk and two of low risk were identified; municipalities forming the clusters of high risk tend to have rural characteristics while the municipalities in the clusters of low risk are located in the two metropolitan areas. The majority of the municipalities forming the clusters of low risk also present higher decreasing trends than the country average.The results presented can contribute to support the development of future interventions on cardiovascular mortality.